Answer:
x = 0 (I must assume you had a typo since c is not a variable in this equation!
Explanation:
Solve for x:
2 (x - 3) + 9 = 3 (x + 1) + x
2 (x - 3) = 2 x - 6:
2 x - 6 + 9 = 3 (x + 1) + x
Grouping like terms, 2 x - 6 + 9 = 2 x + (-6 + 9):
2 x + (-6 + 9) = 3 (x + 1) + x
9 - 6 = 3:
2 x + 3 = 3 (x + 1) + x
3 (x + 1) = 3 x + 3:
2 x + 3 = 3 x + 3 + x
Grouping like terms, 3 x + x + 3 = (3 x + x) + 3:
2 x + 3 = (3 x + x) + 3
3 x + x = 4 x:
2 x + 3 = 4 x + 3
Subtract 4 x from both sides:
(2 x - 4 x) + 3 = (4 x - 4 x) + 3
2 x - 4 x = -2 x:
-2 x + 3 = (4 x - 4 x) + 3
4 x - 4 x = 0:
3 - 2 x = 3
Subtract 3 from both sides:
(3 - 3) - 2 x = 3 - 3
3 - 3 = 0:
-2 x = 3 - 3
3 - 3 = 0:
-2 x = 0
Divide both sides of -2 x = 0 by -2:
(-2 x)/(-2) = 0/(-2)
(-2)/(-2) = 1:
x = 0/(-2)
0/(-2) = 0:
Answer: x = 0